G'Day mate! Here's the answer:
53 1/3
1. 6(3 + 6) - 4/5
2. 6 x 3 is 18, and 6 x 8 is 48
3. 18 plus 48 is 66
4. 66 - 4/5 = 266/5
5. 266/5 as mixed number is 53 1/5
Answer:
1 is 90
2 is 52
Step-by-step explanation:
1 is a right angle so its 90
for 2 angles in a triangle equal to 180
so 180-90-38 is equal to 52
Answer:
y = root under 24 (evaluate it if necessary)
or y = 2 root 6
Step-by-step explanation:
Let the reference angle be x
for the triangle in left,
b = 6-4 = 2
Now,
taking x as refrence angle,
cosx = b/h
or, cosx = 2/h
again,
for the bigger triangle,
taking x as reference angle,
cosx = b/h
or, cosx = b/6
As we can see base of bigger triangle is equal to hypotenuse of triangle at the left,
Let's suppose its a
so, cosx = a/6 = 2/a
now,
a/6 = 2/a
or, a² = 12
now,
for bigger triangle, using pythagoras theorem,
h² = p²+b²
or, 6² = y² + a²
or, 36 = y² + 12
or, y² = 24
so, y = root under 24
Answer: 0.6666666667
Step-by-step explanation: Simplifying
9t + -3t = 4
Combine like terms: 9t + -3t = 6t
6t = 4
Solving
6t = 4
Solving for variable 't'.
Move all terms containing t to the left, all other terms to the right.
Divide each side by '6'.
t = 0.6666666667
Simplifying
t = 0.6666666667
the answer to your question is 13 mm